Treating opioid use disorder with rapid micro induction technique of sublingual buprenorphine/naloxone in an outpatient setting—a case report. Issue 3 (8th June 2022) - Martell, Jose Perez; Konakanchi, Jaya Sri; Sethi, Roopa
Abstract: In this case report, we present a patient on Medication for Opioid Use Disorder (MOUD) for opioid use disorder (OUD) enrolled in an outpatient addictions clinic located inside a metropolitan academic hospital. He had been stable on methadone for more than six years, and had requested to be transitioned to buprenorphine due to economic constraints. He had initially been unsuccessful completing traditional induction due to withdrawal symptoms. By using the rapid micro induction technique, which benefits from the use of ancillary medications for comfort, the patient successfully transitioned to buprenorphine while monitored in the clinic for six days, with fewer reported symptoms of withdrawal. This shows a modified, expedited approach of transition from methadone to buprenorphine after a patient cannot tolerate full abstinence from opioids during traditional induction.